Proximity and size of protected areas in Asian borderlands enable transboundary conservation - Kamath, Vignesh; Oliveras Menor, Imma; Macdonald, David W.; Farhadinia, Mohammad S. (Frontiers in Conservation Science, 2024)
Asia has over 80% of the Earth’s border hotspots for threatened transboundary wildlife, yet only limited research has been done on the distribution of protected areas across international borders in the continent. To address this gap, we conducted a spatial analysis of protected areas across 42 Asian countries. Our study aimed to understand the distribution, proximity, and land-use changes within border protected areas. Two cases were examined, evaluating the spatial relationships at different buffer distances from international borders. Our findings revealed that Asian countries have larger protected areas in borderlands, particularly up to 50 km from borders, as compared to regions further away from the border. Importantly, the median distance between protected areas across international borders is nearly three times shorter than those within the same country. However, the rate of change in natural habitats within protected areas between 2001 and 2019 showed no correlation with their distance from the border. The proximity of protected areas across Asian borders offers opportunities for enhancing connectivity. A larger extent of multi-use protected areas (IUCN1-6+) near borders compared to strict protected areas (IUCN1-4) can facilitate the engagement of communities, which are crucial in transboundary conservation initiatives. Our results can help Asian countries as they work toward their commitments as part of the Kunming–Montreal Global Biodiversity Framework to protect at least 30% of the Earth’s surface area by 2030.